Microbial contamination and disinfection methods of pacifiers - NELSON, Paulo (J Appl Oral Sci, 2015)
OBJECTIVES: To evaluate the microbial contamination of pacifiers by Mutans Streptococci (MS) and the efficacy of different methods for their disinfection. METHODS: Twenty-eight children were assigned to a 4-stage changeover system with a 1-week interval. In each stage, children received a new pacifier and the parents were instructed to maintain their normal habits for 1 week. After this time, the pacifiers were subjected to the following 4 disinfection methods: spraying with 0.12% chlorhexidine solution, Brushtox(®) or sterile tap water, and immersion in boiling tap water for 15 minutes. Microbiological culture for MS and Scanning Electron Microscopy (SEM) were performed. The results were analyzed statistically by Friedman’s non-parametric test (a=0.05). RESULTS: The 0.12% chlorhexidine spray was statistically similar to the boiling water (p>0.05) and more effective than the Brushtox(® )spray and control (p<0.05). The analysis of SEM showed the formation of a cariogenic biofilm in all groups with positive culture. CONCLUSIONS: Pacifiers become contaminated by MS after their use by children and should be disinfected routinely. Spraying with a 0.12% chlorhexidine solution and immersion in boiling water promoted better disinfection of the pacifiers compared with a commercial antiseptic toothbrush cleanser (Brushtox(®)).